"Bei innovativer Forschung ist das Risiko für ein Scheitern naturgemäß erhöht" Interview mit Michael Jungert - Jungert, Michael (INDES. Zeitschrift für Politik und Gesellschaft, 2023)
Keywords: Scheitern in den Wissenschaften; innovative Forschung; Risiko

Das erinnerte Selbst – Personale Identität, Persönlichkeit und autobio-graphisches Gedächtnis - Jungert, Michael (Persönlichkeit. Neurowissenschaftliche und neurophilosophische Fragestellungen, 2014)
Keywords: Persönlichkeit; Personale Identität; Erinnerung; Gedächtnis; Autobiographisches Gedächtnis; Vergessen; Biographische Identität

Editorial: Public Research and Private Knowledge – Science in Times of Diverse Research Funding - Leefmann, Jon; Böttcher, Julia; Jungert, Michael; Merdes, Christoph; Schuol, Sebastian (Frontiers in Research Metrics and Analytics, 2022)

Erkenntnis im Eilverfahren? Wissenschaftsphilosophische Implikationen von »Fast Science« - Jungert, Michael (Wissensproduktion und Wissenstransfer unter erschwerten Bedingungen. Der Einfluss der Corona-Krise auf die Erzeugung und Vermittlung von Wissen im öffentlichen Diskurs, 2022)

Human Nature and Self Design - Jungert, Michael; Bauer, Robert; Schleidgen, Sebastian; Sandow, Verena (Mentis, 2011)
"What is human nature?" is considered to be one of the key questions of anthropology. Throughout history, anthropologists have interpreted this question in different ways and often inferred moral conclusions from their answers. Such discussions about anthropological statements and their moral dimension gain new importance when we think about possibilities of self design brought to us by modern biotechniques. Human traits, so far conceived as unchangeable, are now subject to individual design. For that reason, the traditional questions about human nature and its moral significance have to be reconsidered in new ways. This anthology attempts to clarify some of the problems emerging in this context by reconsidering modern concepts of human nature as broadly as possible. It includes a wide spectrum of aspects concerning human nature and its implications for self design, starting with the discussion of anthropological aspects and extending to embedding present and future biotechniques into ethical analysis.
Keywords: Self design; Human nature; Enhancement; Nature nurture; Bioethics; Neuroprosthetics; body modification

„Ich habe mich sozusagen selbst verloren“ – Biographische Identität, autobiographisches Gedächtnis und Alzheimer-Demenz - Jungert, Michael (Zeitschrift für Praktische Philosophie, 2018)

Interdisziplinarität. Theorie, Praxis, Probleme - Jungert, Michael; Romfeld, Elsa; Sukopp, Thomas; Voigt, Uwe (Wissenschaftliche Buchgesellschaft, 2010)
Der Begriff der ›Interdisziplinarität‹ ist in aller Munde, wird aber nur selten mit der gebotenen Schärfe und Systematik untersucht. Dieser Sammelband unternimmt deshalb den Versuch, prinzipielle Fragen und konkrete Probleme der interdisziplinären Arbeit zu klären. Welche Möglichkeiten und welche Grenzen der fächerübergreifenden Zusammenarbeit gibt es? Welche sprachlichen und methodischen Schwierigkeiten müssen dabei reflektiert werden? Wer solche Fragen erwägt und Antworten darauf sucht, arbeitet mit an einer tragfähigen Grundlage für den fruchtbaren Austausch der Disziplinen, der im Zeitalter globaler Wissensvernetzung immer mehr an Bedeutung gewinnt. Mit Beiträgen von: Ulrich Frey, Ian Hacking, Michael Jungert, Bernulf Kanitscheider, Hilary Kornblith, Winfried Löffler, Thomas Potthast, Elsa Romfeld, Bertold Schweitzer, Thomas Sukopp, Uwe Voigt und Gerhard Vollmer. Mit einem Geleitwort von Klaus Mainzer.
Keywords: Interdisziplinarität; Transdisziplinarität; Multidisziplinarität; wissenschaftliche Kooperation; Wissenschaftsphilosophie

Memory, Personal Identity, and Memory Modification - Jungert, Michael (Selbstgestaltung des Menschen durch Biotechniken, 2015)
Memory, Personal Identity, and Memory Modification: Memory certainly is one of the most significant characteristics of human beings. It is connected with anthropologically essential capabilities like strategic planning, self-reflection, and the development of a unique life story. Although the importance of memory seems to be evident, there is a strong negligence of the role of memory and remembering in theories on personal identity. In this chapter, I will demonstrate that this is mainly due to three factors: 1.) the missing differentiation between various kinds of memory; 2.) the one-sided focus on diachronic identity in the philosophical debate on personal identity; and 3.) the lack of integration of psychological research on memory into philosophical theory. I will discuss how each of these problems should be approached, and outline possible implications for the debate on memory modification and enhancement.
Keywords: Memory; Identity; Person; Personal Identity; Memory modification; Enhancement; Biographical identity; Autobiographical memory; Episodic Memory

Mental realities-the concept of mental disorder and the mind-body problem - Jungert, Michael (Frontiers in Psychology, 2013)
Keywords: concept of mental disorder; reductionism; mind-body problem; PTSD; trauma

Mission: Impossible? On empirical-normative collaboration in ethical reasoning - Schleidgen, Sebastian; Jungert, Michael; Bauer, Robert (Ethical Theory and Moral Practice, 2010)
During the 1980s, empirical social sciences and normative theory seemingly converged within ethical debates. This tendency kindled new debates about the limits and possibilities of empirical-normative collaboration. The article asks for adequate ways of collaboration by taking a closer look at the philosophy of science of empirical social sciences as well as normative theory development and its logical groundings. As a result, three possible modes of cooperation are characterized: first, the empirical assessment of conditions that actually necessitate the translation of normatively derived basic principles into practice rules; second, the empirical assessment of conditions for application of a moral norm which are formulated by bridging principles; third, the empirical assessment of social practice which allows (a) to measure whether adopted norms actually are implemented in practice or not and (b) to encounter new moral problems which are in need of ethical guidance. Finally, the article defends a symbiotic position in Weaver's and Trevino's triad of possible approaches to empirical-normative collaboration in ethics. © 2009 Springer Science+Business Media B.V.
Keywords: Ethik und Empirie; naturalistischer Fehlschluß; Sein-Sollen-Dichotomie; empirical ethics; naturalistic fallacy; empirical-normative collaboration; Hume's Law

Nachgefragt. Einblicke in den Forschungsalltag in der Wissenschaftsreflexion. - Jungert, Michael (2023)
Keywords: Wissenschaftsreflexion; Forschungsfelder; Interdisziplinarität

Neurophilosophy or Philosophy of Neuroscience? What Neuroscience and Philosophy can and can´t do for each other - Jungert, Michael (The Human Sciences after the Decade of the Brain. Perspectives on the Neuro-Turn in the Social Sciences and the Humanities, 2017)
Ever since the rise of modern neuroscience, there has been a controversial discussion about its potential influence on topics that were traditionally seen as part of the domain of social sciences and humanities. At present, the formation of a large number of neuro-hyphenated disciplines such as neuro-theology, neuro-psychoanalysis, or neuro-economics shows the appeal of applying neuroscientific methods to traditional scientific fields. In philosophy, two distinct ways of dealing with the problems and prospects of neuroscience have been developed: While the philosophy of neuroscience tries to apply methods and classical approaches from the philosophy of science to neuroscience, so-called neurophilosophy takes a different approach by applying neuroscientific findings to classical philosophical issues. I evaluate the premises and chances of both approaches by discussing their methods, theoretical assumptions, and explanatory aims. Finally, I will look into neurophilosophy´s claim to integrate neuroscientific findings into philosophical theory by analyzing the relation between memory and personal identity.
Keywords: neurophilosophy; philosophy of neuroscience; autobiographical memory; personal identity; philosophical method; interdisciplinarity

Personen und ihre Vergangenheit.Gedächtnis, Erinnerung und personale Identität - Jungert, Michael (De Gruyter, 2013)
Obwohl der enge Zusammenhang von Gedächtnis, Erinnerung und personaler Identität in der philosophischen Diskussion spätestens seit John Locke weitestgehend unbestritten ist, bleiben die Strukturen und Bedingungen dieses Zusammenhangs zumeist unklar. Dieser Forschungslücke liegen drei Ursachen zugrunde: 1. Die mangelnde Differenzierung zwischen unterschiedlichen Formen von Gedächtnis und Erinnerung, 2. die einseitige Fokussierung auf den Aspekt der diachronen Identität und 3. die fehlende Integration empirischer Ergebnisse in die philosophische Theoriebildung. Der Autor entwickelt auf der Grundlage dieser Problemanalyse einen Ansatz, der die Bedeutung von Gedächtnis und Erinnerung als konstitutive Kriterien personaler Identität aufzuzeigen vermag. Durch die Differenzierung verschiedener Gedächtnisformen, die Charakterisierung der biographischen Identität im Sinne eines evaluativen Selbstverhältnisses von Personen sowie durch die eingehende Berücksichtigung der psychologischen Gedächtnisforschung entsteht eine empirisch fundierte philosophische Theorie zur Rolle von Gedächtnis und Erinnerung bei der Konstituierung und Aufrechterhaltung personaler Identität.
Keywords: Personale Identität; autobiographisches Gedächtnis; biographische Identität; Erinnerung und Identität; John Locke

Public Research and Private Knowledge – Science in Times of Diverse Research Funding - Jungert, Michael; Böttcher, Julia; Merdes, Christoph; Schuol, Sebastian; Leefmann, Jon (Frontiers, 2021)
The production and distribution of knowledge is a key process in scientific and scholarly inquiry. However, this process is not and has never been limited to universities and public research institutes alone, but extends to agents as diverse as the Research & Development Departments of companies, citizen scientists, and private non-profit research institutes. In recent years, these agents have shown an increased interest in basic ˗ as opposed to applied ˗ science, for example in fields of rising social significance such as AI or biomedical technology. These specific research interests in turn direct attention to the sources of funding, and, as a consequence, to the direction of inquiry and the accessibility of results. The main problem that arises from this development can be expressed in two questions: First, does the influence of private funding change the selection of research topics in an epistemically or otherwise (un-) desirable direction? And second, does it lead to a privatization of knowledge, and if so, what are the consequences of this privatization? Some key questions in this area of investigation are: • Where do new sources of research funding come from, and how important a role do they play? Which agents foster the development, which methods do they use, and what are their primary motivations? • What are the epistemic consequences, and who is affected by them? What is the impact of business interests on epistemic norms and ideals, and are there any (additional) sources of bias to be expected? • Have there been any (changes of) institutional structures in the last decades that have stimulated or hindered these tendencies? Which historical idea of science is at stake? Which factors affected the practices of organizing the production and distribution of scientific knowledge during the second half of the 20th century? • Is academic freedom threatened by these developments, and if so, to what extent? How could it be maintained? What are the epistemic effects of endowment chairs and industry-sponsored PhD project
Keywords: public research; private research; research funding; private knowledge; research grants; business interests; scientific knowledge; academic freedom; epistemology

Research Ethics and Scientific Integrity in Neuroscience - Leefmann, Jon; Jungert, Michael (Handbook of Research Ethics and Scientific Integrity, 2019)
With the rise of neuroethics as a research field of its own since the early 2000s, ethical questions concerning the neurosciences have become a major focus of bioethical debate. Yet, the neuroethical discourse has primarily focused on ethical, legal, and social implications of the products of neuroscience research such as clinical interventions and neuro-technologies. Ethical questions concerning the research process in neuroscience have, however, been largely neglected. While topics such as the ethics of test-person recruitment and informed consent procedures, ethics of data sharing and authorship, responsibility for dual use of research results, or the role of ethical review boards are to a large part coextensive with questions in research ethics in other areas of the life sciences, there are still a number of topics distinctive of neuroscience research ethics. These topics will be the focus of this chapter. We will review the debate on disclosure of incidental findings in neuroimaging, discuss the ambivalent role of neuroscience research for informing the ethical standards of animal testing, and finally turn to the debate about responsible research communication and interdisciplinary trespassing in a time of increased public interest in neuroscience research and imagination about its potential social and cultural consequence
Keywords: Scientific Integrity; Incidental Findings; Ethics of Animal Testing; Knowledge Transfer; Neuroscience Imperialism

Review of Martin, J., Bickhard, M. H. (Hg.): The Psychology of Personhood: Philosophical, Historical, Social-Developmental, and Narrative Perspectives - Jungert, Michael (2015)
Keywords: Personhood; Personality; Personal Identity; Philosophy of Psychology

Scheitern in den Wissenschaften. Begriff, Geschichte und Aktualität eines vielschichtigen Phänomens - Jungert, Michael; Schuol, Sebastian (Scheitern in den Wissenschaften. Perspektiven der Wissenschaftsforschung, 2022)
Keywords: Scheitern; Scheitern in den Wissenschaften; Wissenschaftsreflexion; Wissenschaftsforschung; Wissenschaftsphilosophie; Irrtum; Fehler; Fehlerkultur

Scheitern in den Wissenschaften. Perspektiven der Wissenschaftsforschung - Jungert, Michael; Schuol, Sebastian (Mentis/Brill, 2022)
Dieser Band analysiert erstmals systematisch und interdisziplinär Geschichte, Formen, Funktionen und Auswirkungen des Scheiterns im Kontext der Wissenschaften. Das Scheitern ist in seinen unterschiedlichen Erscheinungsformen ein ständiger Begleiter der wissenschaftlichen Praxis. Theorien, Hypothesen oder Experimente einzelner Forscher:innen und Forschergruppen scheitern – vorläufig oder endgültig, partiell oder vollständig. Für ein adäquates Verständnis des wissenschaftlichen Erkenntnisprozesses ist es daher unabdingbar, sich mit den Formen, Funktionen, Mechanismen und Auswirkungen des Scheiterns zu befassen, was bis dato allerdings kaum geschieht – weder innerhalb der wissenschaftlichen Gemeinschaft noch in der öffentlichen Debatte. Durch diese „Vernachlässigung des Scheiterns“ in den Wissenschaften bleiben auch dessen mitunter produktive Effekte zumeist unerwähnt. Über Versuch und Irrtum führen die „Irrwege“ des Erkenntnisprozesses häufig zu Erfolgen und Lösungen. Der Band schließt diese Forschungslücke und verbindet dabei Perspektiven aus vielen Bereichen der Wissenschaftsforschung und aus der Wissenschaftspraxi
Keywords: Philosophie; Wissenschaftsreflexion; Wissenschaftsphilosophie; Wissenschaftsforschung; Philosophy of Science; Scheitern; Fehler; Irrtum; Fehlerkultur

Was ist und zu welchem Zweck betreibt man Wissenschaftsreflexion? - Jungert, Michael; Frewer, Andreas; Mayr, Erasmus (Wissenschaftsreflexion. Interdisziplinäre Perspektiven zwischen Philosophie und Praxis, 2020)
Keywords: Wissenschaftsreflexion; Wissenschaftsphilosophie; Wissenschaftstheorie; Wissenschaft und Gesellschaft

Was wäre eine „erfolgreiche“ Erklärung von Bewusstsein? - Jungert, Michael (Gehirne und Personen. Beiträge zum 8. Internationalen Kongreß der Österreichischen Gesellschaft für Philosophie in Graz, 2008)
Keywords: Phänomenales Bewusstsein; Bewusstsein; Erklärung; Reduktionismus; Naturalismus; Leib-Seele Problem

Was zwischen wem und warum eigentlich? Grundsätzliche Fragen der Interdisziplinarität - Jungert, Michael (Interdisziplinarität. Theorie, Praxis, Probleme, 2010)
Keywords: Interdisziplinarität; Transdisziplinarität

Wissenschaftsreflexion: Bedarf, Konzept und das „Erlanger Modell“ - Jungert, Michael; Geis, Max-Emanuel (Ordnung der Wissenschaft, 2023)
Keywords: Wissenschaftsreflexion; Erlanger Modell; ZIWIS; ZIEW; Wissenschaftsethik

Wissenschaftsreflexion. Interdisziplinäre Perspektiven zwischen Philosophie und Praxis - Jungert, Michael; Frewer, Andreas; Mayr, Erasmus (Mentis/Brill, 2020)
Wissenschaftsreflexion: eine neue interdisziplinäre Perspektive auf die Geschichte, Theorie und Ethik der Wissenschaften sowie auf die praktischen Auswirkungen von wissenschaftlicher Forschung und Erkenntnis. Die Wissenschaften sehen sich gegenwärtig mit Blick auf ihre Geltungs- und Wahrheitsansprüche, ihre Vertrauenswürdigkeit und ihre Rolle in der Gesellschaft vor grundlegende Herausforderungen gestellt. Die Diskussionen betreffen dabei so unterschiedliche Themen wie Unsicherheit, Scheitern oder „Fake News“ in den Wissenschaften, Klimawandel, Gentechnik, Impfungen und Alternativmedizin oder Evolutionstheorien. Nur eine interdisziplinär angelegte Reflexion über die Rolle der Wissenschaften, ihren Erkenntnisanspruch und ihre Methoden wird diesen neuen Herausforderungen gerecht. Mit dem vorliegenden Band wird erstmals der Begriff der Wissenschaftsreflexion differenziert eingeführt und interdisziplinär diskutiert. Der Band umfasst vielfältige Beiträge zu Grundlagen- und Anwendungsfragen aus unterschiedlichen Disziplinen, die gemeinsam eine pluralistische Perspektive eröffnen und konkrete Lösungsmöglichkeiten aufzeigen.
Keywords: Wissenschaftsreflexion; Wissenschaftsgeschichte; Wissenschaftsethik; Wissenschaft und Gesellschaft; Wissenschaft und Paxis; Wissenschaftsphilosophie; Wissenschaftstheorie; Vertrauen in die Wissenschaft; Wissenschaftsskepsis; Wissenschaftskritik

Wissenschaftsreflexion: What is it? Why is it needed? Contemporary Challenges for Studies on Science - Barlösius, Eva; Bogner, Alexander; Butter, Michael; Carrier, Martin; Diehl, Paula; Frei, Nadine; Geis, Max-Emanuel; Jungert, Michael; Leistner, Alexander; Reinhardt, Carsten; Slaatelid, Rasmus; Zürn, Michael (2025)
Contemporary liberal democratic societies exhibit a paradoxical constellation. The scientific knowledge, expertise, and academic education informing them are having ever greater influence socially and politically, which has led to the term “knowledge societies.” Yet science is also increasingly being questioned, delegitimized, and attacked. These attacks are often thought of as heralding the end of the era of the knowledge societies. We submit, however, that such contention characterizes knowledge societies; it articulates the ways in which knowledge societies are socially experienced, which societal distortions are perceived, and how they are combatted. For studies on science the question becomes how to respond to these substantial shifts. We assume that studies on science alone are no longer capable of analyzing the assaults on science and their consequences for science and society. We argue instead for Wissenschaftsreflexion as a highly inclusive approach with a broad disciplinary scope for grappling with this paradoxical constellation in liberal democratic knowledge societies. It is imperative to scrutinize the resulting changes of these contradictory conditions in various social systems—including politics, law, and economics—and the ways in which the changes affect science. We do not claim that wissenschaftsreflexive research is a new field of research or that it competes with established approaches of studies on science. We understand it to be a reflexive attitude toward science in society and toward society in science, a mindset to which scholars should feel committed but which should also be recognized as a social and political task.<br
Keywords: Wissenschaftsreflexion; Wissenschaftsforschung; Science Studies; History of Science; Philosophy of Science